2.M. Workshop: Strategies on preventing and responding to violence and injuries among refugees and migrants. (30th September 2020) - ,; ,
Abstract: Violence, injuries, conflicts and natural disasters are experienced more frequently among migrants and refugees than host population. The objectives of this workshop are to: improve knowledge and understanding among participants on the magnitude and nature of violence, harms and injuries faced by refugees and migrants during their journeys and upon arrival in countries of transit and/or destination in the WHO European Region; raise awareness of the most vulnerable groups across the WHO European Region; discuss strategies and policies to prevent and properly respond to cases of violence; present the new WHO Technical Guidance on Strategies and interventions on preventing and responding to violence and injuries among refugees and migrants and main recommendations from emerging evidence. While the target audience includes policy-makers across sectors at local, national and regional levels, it will also be of value for health-care practitioners, as well as law enforcement and border protection officials. Violence and injuries among refugees and migrants are extremely common and they can take place before departure, during transit and at destination and they can occur for several reasons: boating and traffic accidents, sexual and gender-based violence, exploitation, torture, trafficking, self-directed and collective violence. Member States have promoted many laws and regulations to prevent violence and protect vulnerable groups among refugees and migrants, however the lack of awareness of such legislative mechanisms and the invisibility of many of the form of violence and injury determine serious problems and challenges as well. The current political rhetoric regarding refugees and migrants in Member States is contributing to increase the cases of violence and punitive attitudes against refugees and migrants. Key messages: Stakeholders need to strengthen the knowledge base on violence and injury experienced by refugees and migrants and act in accordance with the latest evidence, international norms and standards. States should ensure safe passage, address causes of violence and injuries in transit and destination countries (prevention); identify victims, provide care; investigate and prosecute perpetrators.